THE COGNITIVE LOAD OF SIMULTANEOUS INTERPRETATION:A COMPARATIVE ANALYSIS OF SYNTACTIC ASYMMETRY IN ENGLISH -GERMAN AND ENGLISH -UZBEK LANGUAGE PAIRS (International journal of artificial intelligence, 2026)
Simultaneous Interpretation (SI) represents one of the most taxing cognitive activities known to human linguistics. This study investigates the impact of syntactic asymmetry—specifically the divergence between SVO (Subject-Verb-Object) and SOV (Subject-Object-Verb) structures—on the cognitive load of interpreters. By comparing English-German and English-Uzbek interpretation contexts, this paper analyzes the "Ear-Voice Span" (EVS) and the strategies of anticipation. Findings suggest that the "verb-late" nature of Uzbek and German necessitates a higher reliance on working memory compared to symmetrical language pairs. The research utilizes recent data from 2020–2025 to evaluate the efficacy of "probabilistic prognosticating" in SI.